Pengaruh Kombinasi Biskuit Ikan Gabus dan Ubi Jalar Ungu Terhadap Berat Badan Anak Usia 12 - 36 Bulan di Puskesmas Wilayah Kerja Purwadadi - Mela Mustika Sari; Siti Sugih Hartiningsih; Herri S Sastramihardja (Akademi Kebidanan La Tansa Mashiro, 2022)
The issue of nutrition in population development is still an issue that is considered to be a major problem in the world population order, biscuits based on cork fish, and brown rice can improve weight gain. The purpose of this study was to determine the effect of Cork and Purple Sweet Potato biscuits on weight gain. The provision of cork and sweet potato biscuits was given to children aged 12-36 months at Health Center Subang, from July to August 2018. The purpose of this study was to determine the effect of cork fish and purple sweet potato biscuits on the weight gain of children aged 12 36 months. The research method used was quantitative, a quasi-experimental research design with a pretest-posttest control group design approach, with a sample of 64 toddlers aged 12-36 months. The sampling technique in this study was probability with randomization type, children under five who met the inclusion criteria of each intervention group amounted to 32 samples. Analysis of the effect of body weight using the T statistical test to determine the effect of giving biscuits a combination of snakehead fish and purple sweet potato. The results of the study showed an increase in body weight in the intervention group with an average increase of 6.65%, whereas in the control group had an average value of 1.15%. In addition, the results of data analysis using the T test obtained a value (p lt;0.05) there were differences in underweight weight gain after being given intervention in the form of cork fish biscuits and purple sweet potato It is expected that further research will be continued by exploring other factors related to improving infant nutrition and further research on the efficient time for giving cork fish and purple sweet potato biscuits in order to obtain more optimal results.